EFEKTIVITAS PROGRAM ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) NASIONAL DALAM PENINGKATAN PELAYANAN PUBLIK DI KABUPATEN SUMEDANG - Putra Pratama Wijaya; Arip Rahman Sudrajat; Anne Friday Safaria (LPPM UNSAP & FISIP UNSAP, 2023)
This research aims to find out and analyze the effectiveness of the electronic traffic law enforcement program implemented by the Sumedang Police. The research method used is a qualitative research method. Sample determination was carried out using purposive sampling. This research was analyzed using descriptive qualitative research with research informants from the Sumedang Resort Police. The research was conducted using case studies and the Miles and Huberman model with steps including data reduction, data presentation and drawing conclusions. The results of the research show that the people of Sumedang do not fully comply with traffic regulations as stated in Law No. 22 of 2009 concerning traffic and road transportation. The suggestions from this research are that the Sumedang Resort Police need to take a comprehensive approach in planning and budget allocation, increase active community participation through an integrated educational approach, and carry out cross-sector coordination in program implementation.